Digital Communication through Online Learning in Indonesia: Challenges and Opportunities - Ayu Rahmawati; Firman Kurniawan Sujono (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2021)
The technological revolution that has changed from analog to digital creates new challenges and opportunities, particularly when referring to the communication perspective. This study discusses communication through digital media and its dynamics in Indonesia. It comprehensively examined Ruangguru, the biggest online learning platform in Indonesia. This paper uses a qualitative descriptive approach with a case-study method. It is aimed to analyze Ruangguru’s online learning communication patterns using the social presence theory in the dimensions of social context, online communication, and interactivity. The result of this study reveals many advantages offered by online learning. Nevertheless, online learning can not fully replace conventional learning, especially when viewed from the low dimensions of social context. In the online communication dimension, Indonesia is still hampered by technical problems, both from technology infrastructure and the readiness of teachers and students.